Association between polymorphisms of exon 12 and exon 24 of JHDM2A gene and male infertility - Zohreh Hojati; Fatemeh Nouri Emamzadeh; Fariba Dehghanian (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2016)
Background: Some dynamic changes occurs during spermatogenesis such as histone removal and its replacement with transition nuclear protein and protamine. These proteins are required for packing and condensation of sperm chromatin. JHDM2A is a histone demethylase that directly binds to promoter regions of Tnp1 and Prm1 genes and controls their expression by removing H3K9 at their promoters. Objective: The association between polymorphisms of exon 12 and exon 24 in JHDM2A gene and male infertility were evaluated for the first time. Materials and Methods: In this experimental study, 400 infertile men (oligospermia and azoospermia) and normal healthy fathers were evaluated (n=200). Single Strand Conformation Polymorphism (SSCP-PCR) and polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) methods were used for screening any polymorphisms that are exist in exon 12 and exon 24. Results: Exon 24 PCR products were analyzed by RFLP but no polymorphism was found in this exon at the restriction site of EcoRV enzyme. Our monitoring along the whole nucleotides of exon 12 and exon 24 were continued using SSCP method, but we found no change along these exons. Conclusion: Generally, this study evaluated the association between polymorphisms in exon 12 and exon 24 of JHDM2A gene and male infertility which suggests that polymorphisms of these exons may not be associated with the risk of male infertility.